Iran And Southeast Asia: An Analysis Of Iran's Policy Of "Look To The East" - Soltaninejad, Mohammad (Penerbit Universiti Sains Malaysia (USM Press), 2017)
This article studies the sudden rise in the economic and commercial relations between Iran and Southeast Asian countries from 2007 to 2011 and its collapse afterwards. The author attributes this phenomenon to two factors: first, politics' priority over economy in Iran's foreign policy during the years Iran adopted the policy of "Look to the East," and second, characteristics of Iran's relations with the great powers of the United States and China. Based on these, the author contends that Iran's bid to establish firm economic relations with the East in order to manage and reduce political pressures from the West is the reason for sudden rise in Iran-Southeast Asia relations. The rising trend in the relations was reversed from 2011 onward mainly due to the United States' persuasion of the Southeast Asian countries to reduce cooperation with Iran. The author further discusses that the dynamics of Iran-China relations have also limited the scope of Iran-Southeast Asia cooperation.